Theoretical studies and rational design of symmetrical and unsymmetrical squarine dyes: An application for dye-sensitized solar cell / Ameerul Hazeeq Hashim - Ameerul Hazeeq , Hashim (2020)

(untitled)
Dye- sensitized solar cell (DSSC) has been explored in depth due to its effectiveness and low-cost conversion of photovoltaic energy. Squarine has unique properties because it has the capacity to increase light-harvesting energy as well as its low-cost conversion of photo-energy. Dyes that perform well, namely the symmetrical indolenine-based squaraine dye (SQM1a, VG1, and VG10) and the unsymmetrical indolenine-based squaraine dye (SQM1b, SQ01, MSQ, and VG13) were computationally studied and modified. Six density functionals were used to verify the accuracy of the simulation ranging from generalized gradient approximation (pure-GGA) density functional to the large Hartree-Fock exchange functional. Three methods were used to benchmark oxidation potential for all seven dyes namely, the vertical ground state oxidation potential (GSOPv), adiabatic ground state oxidation potential (GSOPa) and Koopman’s Theorem. Calculation for oxidation potential via GSOPv using M062X has provided better correlation to experimental oxidation potential energy level with mean absolute error of 0.0081 eV. Following the success in benchmarking experimental oxidation potential energy level, GSOPv was employed using M062X hybrid meta-GGA functional as part of the advanced theoretical methods to modify squarine dye structure via Dewar’s rule. SQM1a was modified by addition of either electron donating (ED) or electron-withdrawing (EW) substituent along the π-conjugated bridge. Methoxy (-OCH3) and nitrile (-CN) were chosen as the ED unit and EW unit respectively. As a consequence, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy levels were altered for band gap optimization.